ANTIBACTERIAL TESTING OF MORINGA OLEIFERA LEAF EXTRACT AGAINST STREPTOCOCCUS MUTANS ATCC® 25175™ - Muhammad Ichsan; Cut Soraya; Zaki Mubarak; Syahrun Nur; M. Riza Pahlevi (PT. Radja Intercontinental Publishing, 2024)
This study evaluates the antibacterial activity of Moringa oleifera leaf extract against Streptococcus mutans ATCC® 25175™. Leaf extracts from mountainous and coastal areas were tested using maceration with 96% ethanol, dilution for Minimum Inhibitory Concentration (MIC) and Minimum Bactericidal Concentration (MBC), and disk diffusion for inhibition zones. Results showed that the mountainous extract was more effective, with a maximum inhibition zone of 18.38 mm and MBC of 100%, compared to the coastal extract with an inhibition zone of 12.94 mm and MBC of 75%. This study highlights the potential of Moringa oleifera leaf extract as a natural antibacterial agent for mouthwash development.